NARA: Network Assisted Routing and Allocation Algorithm for D2D Communication in 5G Cellular Networks - BASTOS, A. V. (Stefan cel Mare University of Suceava, 2021)
This work presents the Network Assisted Routing and Allocation Algorithm (NARA), a routing and allocation algorithm for device-to-device (D2D) communication in 5G cellular architectures. NARA algorithm is a new routing and resource block allocation algorithm that aims at reducing the impact of interference and extends network coverage in D2D communications. We model the allocation of resource blocks as a Minimum Graph Coloring Problem. As baselines, we compare the proposed strategy to NAR-G, a previous version that uses a greedy allocation heuristic; MaxC/I, a reference heuristic for resource allocation; and LBS-AOMDV for routing. The results reveal that NARA reduces message loss in 47.4% when compared LBS-AOMDV, 39.87% to NAR-G, and 23.06% when compared to MaxC/I. As for allocation, NARA provides 23.05% more D2D flows than MaxC/I.